2023
DOI: 10.3389/fenvs.2023.1130443
|View full text |Cite
|
Sign up to set email alerts
|

Research on lake water level and its response to watershed climate change in Qinghai Lake from 1961 to 2019

Abstract: Lake water level reflects the dynamic balance of water input and output/loss and is a sensitive indicator of climate change and variation. Studying the relationship between the closed Qinghai Lake water level and watershed climate change is important for understanding regional climate change and its impacts on the lake. The objective of this study was to investigate changes in Qinghai Lake water level/area and environmental factors during 1961–2019, using ground-based measurements data, hydrological balance mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…From south to north, it converges with the Yangtze River near Shizhong Mountain in Hukou County, Jiujiang City. At normal water levels (14-15 m), the lake's surface area is 3150 km 2 . During high water levels (20 m), it exceeds 4125 km 2 , while at low water levels (12 m), it is reduced to only 500 km 2 .…”
Section: Research Areamentioning
confidence: 99%
See 2 more Smart Citations
“…From south to north, it converges with the Yangtze River near Shizhong Mountain in Hukou County, Jiujiang City. At normal water levels (14-15 m), the lake's surface area is 3150 km 2 . During high water levels (20 m), it exceeds 4125 km 2 , while at low water levels (12 m), it is reduced to only 500 km 2 .…”
Section: Research Areamentioning
confidence: 99%
“…At normal water levels (14-15 m), the lake's surface area is 3150 km 2 . During high water levels (20 m), it exceeds 4125 km 2 , while at low water levels (12 m), it is reduced to only 500 km 2 . Poyang Lake plays a crucial role in regulating the water level of the Yangtze River, conserving water resources, improving the local climate, and maintaining the ecological balance in surrounding areas.…”
Section: Research Areamentioning
confidence: 99%
See 1 more Smart Citation
“…The main factors affecting the changes in water quantity in Qinghai Lake are precipitation (P), evaporation (E) and runoff into the lake (R s ) [24]. Most previous studies qualitatively revealed that the increase in P and R s was significantly positively correlated with the lake water level, while the increase in E inhibited the increase in the lake water level [19,[25][26][27][28][29][30][31]. Li et al (2020) concluded that the influence of last year's factors (R s , P and E) on the water level was more significant than that of the current year, and further quantitatively evaluated the contribution rate of the three variables to the water level fluctuation of Qinghai Lake from 1961 to 2015 by using the principle of water balance and correlation coefficients as R s > P > E. For the same research period, Wang and Gao (2021) conducted work based on the study of Li (2020) and further demonstrated through the quantitative analysis of ridge regression that the contribution rate of the three variables to the water level fluctuation of Qinghai Lake was R s (38.2%) > E (31.4%) > P (30.4%).…”
Section: Introductionmentioning
confidence: 99%
“…Herrnegger et al ( 2021 ).8Soja et al ( 2013 ). 9Li et al ( 2023 ).10 Abbott and Anderson ( 2009 ). 11 UNEP-DHI Centre on Water and Environment ( 2021 ).12Bali ( 2022 ).13Beutel et al ( 2001 ).…”
mentioning
confidence: 99%